The Effect Of Increasing Servicescape And Modernizing Petrol Station Services On Pertamax Series Purchase Decisions Through Perceived Value: Systematic Literature Review (SLR) Mediation With Bibliometrics - Surya Suganda; Budi Eko Soetjipto; Madziatul Churiyah (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the effect of increasing servicescape and modernization of Public Fuel Filling Station (SPBU) services on the purchase decision of Pertamax Series products with perceived value as a mediating variable. This study uses a Systematic Literature Review (SLR) approach combined with bibliometric analysis to identify, map, and synthesize relevant research developments related to the quality of the service environment, modernization of fuel retail services, perceived value by consumers, and purchasing decisions. Research data was obtained from various reputable scientific articles indexed in academic databases such as Scopus and Google Scholar with a range of publications of the last ten years. The literature selection process is carried out systematically through the stages of identification, screening, feasibility, and inclusion using the PRISMA guidelines. Bibliometric analysis is used to map research trends, author collaboration, and keyword linkages analyzed using VOSviewer software. The results of the study show that increasing servicescape such as facility comfort, cleanliness, physical design, and the availability of supporting facilities is able to increase consumer perception of gas station services. In addition, service modernization through payment digitalization, self-service systems, and technology-based service innovations also strengthen customer experience. The combination of these two factors has been proven to increase perceived value which ultimately encourages consumers to make a decision to purchase Pertamax Series products. The findings of this study make a conceptual contribution to the development of a study of consumer behavior in the energy retail sector and provide practical implications for petrol station managers in designing strategies to improve service quality and modernize facilities to increase consumer preference for high-quality fuels.